Alteration of Transforming Growth Factor β Signaling Pathway Predicts Worse Prognosis in Pancreatic Ductal Adenocarcinoma. Issue 4 (April 2020) - Li, Mao; Li, Ang; Zhao, Xiaochen; Hou, Shengzhong; Lu, Shan; Mou, Yu; Liu, Xubao; Cai, Shangli; Cao, Dan; Tian, Bole
Abstract : Objectives: Transforming growth factor β (TGF-β) signaling pathway is one of the core pathways in pancreatic ductal adenocarcinoma (PDAC). Prognostic value of TGF-β pathway genes as a functionally related group in PDAC is rarely studied. Methods: Seventy-two PDAC patients who underwent surgery between November 30, 2015, and September 13, 2017, in West China Hospital, Sichuan University, were identified and included in this study. Whole-exome sequencing or targeted next-generation sequencing was performed with tumor tissue. Clinicopathologic characteristics and survival data were retrospectively collected and analyzed. Results: Genetic alterations were detected in 71 patients (98.6%). Although 1 patient (1.4%) had one genetic alteration, 33 patients (45.8%) had 2 to 4 alterations and 37 patients (51.4%) had 5 or more alterations. Twenty-five patients with TGF-β pathway alteration were identified as TGF-βm+ group. Other 47 patients were TGF-βm− group. Mutation of TGF-β pathway was independently associated with inferior survival (hazard ratio, 2.22, 95% confidence interval, 1.05–4.70, P = 0.04), especially in patients accepting radical surgery (hazard ratio, 3.25, 95% confidence interval, 1.01–10.49, P = 0.04). Conclusions: Inferior prognosis was observed in PDACs with mutations of TGF-β pathway. Genomic information could help screen out patients at risk after surgery, and adjuvant therapy might benefit this subgroup of PDACs. Abstract : Supplemental digital content is available in the text.